Harmonic Matrix and Harmonic Energy - LI Bingjun (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
We define the Harmonic energy as the sum of the absolute values of the eigenvalues of the Harmonic matrix, and establish some of its properties, in particular lower and upper bounds for it.